Linking autophagy and metabolism in plasmacytoid dendritic cells - Silva, Carlota Ramalhinho Piteira Liques da (2021)
Autophagy is a cellular housekeeping mechanism that degrades long-lived redundant and malfunctioning cellular components. It has a vital role in the immune system, not only for being directly involved in the elimination of pathogens, but also through the functional regulation of immune cells, including dendritic cells (DCs). DCs are phagocytic, antigen presenting cells, which connect the innate response with adaptive immunity, by priming naïve T cells and directing the ensuing polarization. Plasmacytoid DCs (pDCs) are a subpopulation of DC specialized in the rapid production of type I interferon, making them particularly relevant in antiviral responses. Their activation and functional response appear to be strongly dependent on the autophagic flux, which led us to investigate if cellular metabolism could play a role in the regulation of pDC autophagy and, thus, in their function. To that end, a pDC cell line (CAL-1) was treated with three different autophagy inhibitors: Spautin-1, VPS34-IN1 and Bafilomycin A1, followed by Western blot analysis of LC3 lipidation, to confirm autophagy inhibition, and 1H NMR metabolomics. The three drugs efficiently inhibited autophagy and affected the cellular metabolism in a significant manner. Interestingly, the effects of the different inhibitors on the cells metabolic profile were very different. Bafilomycin A1 had the least impact on the cells, while Spautin-1 and VPS34-IN1 had a stronger influence on metabolism, albeit in different directions. While Spautin-1 stimulated glycolysis, impaired the TCA cycle, decreased the levels of amino acids, and increased the levels of branch-chained ketoacids, suggesting mTORC1 activation, VPS34-IN1 caused opposite variations, which suggested AMPK activation. As for Bafilomycin A1, it appeared to induce early endoplasmic reticulum (ER) stress responses, with a mild increase in amino acids, uridine nucleotides, ATP, and NAD+. Overall, this work demonstrated the metabolic responses of pDC cells to autophagy inhibition to be highly dependent on the specific inhibitor considered, raising new questions about the molecular targets and mechanisms involved. Their improved understanding in the future will be key to advance knowledge on pDC biology and functional behaviour.